2006
DOI: 10.1016/j.mod.2005.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Msx1 and Dlx5 act independently in development of craniofacial skeleton, but converge on the regulation of Bmp signaling in palate formation

Abstract: Msx and Dlx homeoproteins control the morphogenesis and organization of craniofacial skeletal structures, specifically those derived from the pharyngeal arches. In vitro Msx and Dlx proteins have opposing transcriptional properties and form heterodimeric complexes via their homeodomain with reciprocal functional repression. In this report we examine the skeletal phenotype of Msx1; Dlx5 double knock-out (DKO) mice in relationship with their expression territories during craniofacial development. Co-expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
1
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 60 publications
5
58
1
3
Order By: Relevance
“…8E,G). Levi et al (Levi et al, 2006) reported wholemount in situ hybridization results for Bmp4 mRNA expression in the E13.5 palate and also clearly showed a strong Bmp4 expression domain in the posterior palate (Levi et al, 2006). We carried out section in situ hybridization of the whole series of frontal sections of E13.5 mouse palate and confirmed the separate Bmp4 mRNA expression domains in the anterior and posterior regions of the palatal shelves (Fig.…”
Section: Research Articlesupporting
confidence: 64%
See 1 more Smart Citation
“…8E,G). Levi et al (Levi et al, 2006) reported wholemount in situ hybridization results for Bmp4 mRNA expression in the E13.5 palate and also clearly showed a strong Bmp4 expression domain in the posterior palate (Levi et al, 2006). We carried out section in situ hybridization of the whole series of frontal sections of E13.5 mouse palate and confirmed the separate Bmp4 mRNA expression domains in the anterior and posterior regions of the palatal shelves (Fig.…”
Section: Research Articlesupporting
confidence: 64%
“…8I,K,M). Moreover, Levi et al (Levi et al, 2006) showed that Bmp4 mRNA expression in the anterior palate, but not in the posterior palate, was reduced in the Msx1 −/− embryos in comparison with wild-type control embryos (Levi et al, 2006). We found that the posterior domain of Bmp4 mRNA expression was significantly downregulated in the Pax9 del/del mutant embryos, indicating that Pax9 regulates Bmp4 expression in the posterior palate independently of Msx1.…”
Section: Research Articlementioning
confidence: 62%
“…Inactivation of Dlx5 leads to an expansion of the oral region of the palatal shelf Previous studies examining Dlx5 -/-mice were based on skeletal staining, which revealed incomplete palatal bone fusion (Depew et al, 1999;Levi et al, 2006). In order to characterize the palatal phenotype thoroughly, we performed scanning electron microscopy (SEM) on Dlx5 -/-mice.…”
Section: Oronasal Patterning Of Mouse Palatal Mesenchymementioning
confidence: 99%
“…For each probe, two normal and two mutant specimens were examined. Section and whole-mount hybridization was done according to published procedures (Levi et al, 2006).…”
Section: Immunohistochemistry and In Situ Hybridizationmentioning
confidence: 99%